Analisis pengaruh variabel makro dan mikro ekonomi terhadap penghimpunan zakat di Indonesia - Rohman, Catur Hidayatur; Afandi, Akhsyim (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Islam is a religion of rahmatan lil 'alamin, meaning that Islam is a mercy and goodness for the entire universe. This study analyzes the influence of macro and microeconomic variables on zakat collection in Baitul Maal Hidayatullah for the period 2016-2021. Macro and microeconomic factors include Gross Regional Domestic Product (GRDP), Poverty, Gold Price, Provincial Minimum Wage (UMP). This study used the kuantitative method with panel data approach with an estimated Generalized Method of Moment (GMM) model involving 30 provinces in Indonesia that already have LAZ Baitul Maal Hidayatullah (BMH) Representatives for the period 2016-2021. The results of this study show that GRDP and Poverty have a significant positive influence, while Gold Price have a negative influence, and UMP have a positive but insignificant influence.